Applications of automatic identification technologies in manufacturing: a framework for implementation. (4th August 2014) - Park, Taeho; Kim, Mohan
In the past, automatic identification (AutoID) technologies were utilised primarily for data acquisition or for the automatic identification of products or objects in non–manufacturing operations and industries. They were also perceived as a suitable replacement for manual or keyboard data entry. However, the technologies have recently been applied in many other manufacturing operations, such as inventory control, shipping/receiving, security, preventive maintenance, personnel management, job scheduling, and shopfloor control. In light of the growing number of applications of AutoID technologies in the manufacturing area, a questionnaire survey and interviews with Silicon Valley companies were conducted to study the implementation of these new technologies in the manufacturing industry. The survey and interview results were presented herein, including an illustration of the current trend toward AutoID technology usage, its benefits, applications in manufacturing, implementation problems, and key elements deemed necessary for its successful implementation. Finally, a proposal outlining the planning and implementation of AutoID technologies within the manufacturing sector is presented.